MICROBIOLOGICAL CHARACTERISTICS OF THE REPRODUCTIVE TRACT IN WOMEN WITH AND WITHOUT CHRONIC ENDOMETRITIS - E. G. Kobaidze; M. M. Padrul (Акушерство, гинекология и репродукция)
Chronic endometritis (CE) is one of the most common disorders of the female reproductive system. Identification of the infectious cause of CE remains a persistent problem, especially in light of the recent concept of the microbiome. The aim of the study was to evaluate the microbiome in the cervical canal and uterine cavity in patients with CE compared with CE-free women. Materials and methods. A total of 75 women of reproductive age were examined: of those, 33 were CE-free (group 1) and 42 – diagnosed with CE (group 2). To study the microbiological characteristics of the genital tract, we used our original technique able to minimize contamination of uterine samples by cervical microflora. Results. In both groups of women, positive growth of microflora (mostly, Lactobacillus) in either cervical or uterine cavity samples was found. In women with CE, a different type microflora dominated: thus, in every 8th patient of group 2, the cervical canal samples contained β-lactamase producing by Escherichia coli, which indicated a highly rational antibiotic therapy. Conclusion. We propose that the somatic status plays a crucial role in the overall body response to a pathogenic microorganism. In our study, the microbiomes of the endometrium and the cervix were similar, but not identical; there were differences between the women with different medical conditions.